Management practices and M&A success - Delis, Manthos D.; Iosifidi, Maria; Kazakis, Pantelis; Ongena, Steven; Tsionas, Mike G. (Journal of Banking & Finance, 2022)
We study whether management practices determine merger and acquisition (M&A) success. We model management as an unobserved (latent) variable in a standard microeconomic model of the firm and derive firm-year management estimates. We validate these estimates against benchmark survey data on management practices and by using Monte Carlo simulation. We show that our measure is among the most important determinants of value creation in M&A deals, substantially increasing the predictive power of models that explain cumulative abnormal returns. Thus, we offer a measure of management practices that identifies the best-performing M&As. Our results are robust to the inclusion of acquirer fixed effects and many control variables, and to several other sensitivity tests. We identify the Q-theory as the key mechanism driving our results.